Spirituality and transformative learning in health context. - Ahmad, Farizah; Muhamad, Mazanah; Idris, Khairuddin; Abdullah, Amini Amir; Hashim, Zailina (2007)
Spiritual dimension of adult learning is beginning to enter the domain of research but is not very visible in the literature yet. Attending to the spiritual dimension of adult learning has been suggested as part of respecting the learner as the author of her/his own life in the quest for meaning. In the health context, spirituality is increasingly recognized as an important resource for patients learning to live with challenges of life-threatening illness such as breast cancer. The learning experience is also often transformational. This literature review seeks to explicate the concept of spirituality and transformative learning in the health context. The purpose is to provide understanding the importance of spirituality and spiritual learning processes in the lives of breast cancer survivors. The focus,here is also to provide an awareness of Islamic perspectives of spirituality and transformative learning. The literature suggests that cancer survivors' experiences with cancer and their learning processes must be understood within the appropriate cultural context. This is especially so for spirituality. The common emphasis of spirituality on relationship to God, self and to others, may significantly influence how people learn living with cancer.